The Intersection between Ocular and Manual Motor Control: Eye–Hand Coordination in Acquired Brain Injury - Rizzo, John-Ross; Hosseini, Maryam; Wong, Eric A.; Mackey, Wayne E.; Fung, James K.; Ahdoot, Edmond; Rucker, Janet C.; Raghavan, Preeti; Landy, Michael S.; Hudson, Todd E. (Frontiers in Neurology, 2017)
Acute and chronic disease processes that lead to cerebral injury can often be clinically challenging diagnostically, prognostically, and therapeutically. Neurodegenerative processes are one such elusive diagnostic group, given their often diffuse and indolent nature, creating difficulties in pinpointing specific structural abnormalities that relate to functional limitations. A number of studies in recent years have focused on eye-hand coordination in the setting of acquired brain injury (ABI), highlighting the important set of interconnected functions of the eye and hand and their relevance in neurological conditions. These experiments, which have concentrated on focal lesion-based models, have significantly improved our understanding of neurophysiology and underscored the sensitivity of biomarkers in acute and chronic neurological disease processes, especially when such biomarkers are combined synergistically. To better understand eye-hand coordination and its connection with ABI, there is a need to clarify its definition and to delineate its neuroanatomical and computational underpinnings. Successful eye-hand coordination relies on the complex feedback- and prediction-mediated relationship between the visual, ocular-motor, and manual motor systems and takes advantage of finely orchestrated synergies between these systems in both the spatial and temporal domains. Interactions of this type are representative of functional sensory-motor control, and whose disruption constitutes one of the most frequent deficits secondary to brain injury. The present review describes the visually mediated planning and control of eye movements, hand movements, and their coordination, with a particular focus on deficits that occur following neurovascular, neurotraumatic, and neurodegenerative conditions. Following this review, we also discuss potential future research directions, highlighting objective eye-hand coordination as a sensitive biomarker complement within acute and chronic neurological disease processes.